Analysis Of Ontology, Epistemology and Axiology Of Balaghah Science In Arabic (A Study Of Philosophy Of Science) - Anisah, Suria; Ramadhan, Fadhli (Asosiasi Ahli Filsafat Keilahian Indonesia, 2024)
The science of Balaghah is very famous for Arabic language learners so many have researched related to the existence of this science in strengthening the context of Arabic language learning. In this case, researchers also do the same thing, namely conducting research related to Balaghah Science which relates to Philosophy of Science material that discusses ontology, epistemology, and axiology. The purpose of this research is to find out the ontology, epistemology, and axiology contained in Balaghah Science. This type of research is descriptive qualitative research with the research method used by the author being a literature study or literature study. The results of this study found that the ontology of Balaghah science concerns the nature of what will be studied and highlights the existence and nature of rhetorical reality, epistemology focuses on how Balaghah knowledge is obtained and the use of Balaghah science, while axiology evaluates ethical and aesthetic values in delivering messages. Axiology is also concerned with assessing the beauty and values contained in the use of language.